Preservation of quality of life in patients with human epidermal growth factor receptor 2–positive metastatic breast cancer treated with tucatinib or placebo when added to trastuzumab and capecitabine (HER2CLIMB trial). (August 2021) - Mueller, Volkmar; Wardley, Andrew; Paplomata, Elisavet; Hamilton, Erika; Zelnak, Amelia; Fehrenbacher, Louis; Jakobsen, Erik; Curtit, Elsa; Boyle, Frances; Harder Brix, Eva; Brenner, Andrew; Crouzet, Laurence; et al.
Abstract: Aims: In HER2CLIMB, tucatinib significantly improved progression-free and overall survival in patients with human epidermal growth factor receptor 2–positive (HER2+) metastatic breast cancer. We evaluated the impact of tucatinib on health-related quality of life (HR-QoL) in HER2CLIMB. Methods: Patients were randomised 2:1 to tucatinib or placebo combined with trastuzumab and capecitabine. Starting with protocol version 7, the EuroQol 5 Dimensions 5 Levels (EQ-5D-5L) questionnaire and EQ visual analogue scale (VAS) were administered at day 1 of cycle 1, every two cycles during cycles 3–9, every three cycles during cycle 12 and thereafter and at each patient's 30-day follow-up visit. Results: Among 364 patients eligible for HR-QoL assessment, 331 (91%) completed ≥1 assessment. EQ-VAS scores were similar for both arms at baseline and maintained throughout treatment. EQ-5D-5L scores were similar between the treatment arms, stable throughout therapy and worsened after discontinuing treatment. Risk of meaningful deterioration (≥7 points) on EQ-VAS was reduced 19% in the tucatinib vs. placebo arm (hazard ratio [HR]: 0.81; 95% confidence interval [CI]: 0.55, 1.18); the median (95% CI) time to deterioration was not reached in the tucatinib arm and was 5.8 months (4.3, -) in the placebo arm. Among patients with brain metastases ( n = 164), risk of meaningful deterioration on EQ-VAS was reduced 49% in the tucatinib arm (HR: 0.51; 95% CI: 0.28, 0.93); the median (95% CI) time to deterioration was not reached in the tucatinib arm and was 5.5 months (4.2, -) in the placebo arm. Conclusions: HR-QoL was preserved for patients with HER2+ metastatic breast cancer who were treated with tucatinib added to trastuzumab and capecitabine and maintained longer with tucatinib therapy than without it among those with brain metastases. Clinical Trial Registration: NCT02614794 Highlights: HR-QoL was preserved in HER2+ metastatic breast cancer patients on a tucatinib regimen. HR-QoL was preserved longer in patients with brain metastases taking tucatinib. Preserved HR-QoL was in context of improved progression-free and overall survival.